Absorbance study on the adsorptive removal of Fe(III) ions using activated carbon from coconut shells - Otong Nurhilal; Adam Bagaskara; Aufa Haritsah Sihite; Sahrul Hidayat; Setianto Setianto (Current Research in Green and Sustainable Chemistry)
This study explores the adsorption kinetics and capacity of Fe(III) ions from aqueous solutions onto activated carbon synthesized from coconut shells. The carbonization process was conducted at 700 °C for 1 h, followed by activation with zinc chloride (ZnCl2) as the activating agent. The resulting activated carbon was characterized using nitrogen adsorption isotherms, X-ray diffraction (XRD), and scanning electron microscopy coupled with energy-dispersive X-ray spectroscopy (SEM-EDS). The absorbance of Fe(III) solutions was quantitatively analyzed using UV–Vis spectroscopy. Activated carbon derived from coconut shells was employed as an adsorbent for Fe(III) Nitrate solutions. The study systematically investigated several parameters influencing the adsorption process, including initial ion concentration, contact time, and varying weights of activated carbon. Characterization results indicated a specific surface area of 490.29 m2/g, with a predominately amorphous aromatic carbon structure and a carbon content of approximately 86.41 % by weight. The maximum adsorption capacity for Fe(III) Nitrate was observed to be 60.95 mg/g for a carbon weight of 0.005 g and 50.95 mg/g for a carbon weight of 0.01 g. Notably, the highest removal efficiency reached 83.81 % with an activated carbon weight of 0.5 g.